Correlating the level of patients’ self-efficacy with paternalistic, consumerist, participative and training doctor relationships in dental offices - Lucian Josan; Alina Ormenisan; Iulia Dumitrescu; Mariana Pacurar (Romanian Journal of Stomatology)
Self-efficacy—the belief in using abilities for a specific purpose—is an indicator of engagement. Self-efficacy anticipates the positive results of the actions undertaken due to the knowledge and skills possessed. Within the concept of self-efficacy, we will also mention generalized self-efficacy, i.e. a person's view of himself as capable of effectively performing a wide variety of tasks and performing in a wide variety of situations. Self-efficacy has an important role in learning and developing new skills and knowledge; this applies both to patients and to the doctor or medical staff. Perceived self-efficacy helps to account for such diverse phenomena as changes in coping behavior produced by different modes of influence, the level of physiological stress reactions, self-regulation of refractory behavior, resignation and discouragement from failure. By making a correlation between self-efficacy and the patient's behavior, we can also ascertain the psychobehavioral effect this has on the patient. The quantification of the patient's self-efficacy level is directly proportional to his possibility to overcome the disease along with the involvement of other direct or indirect factors. The study was carried out on a group of 157 patients (age range 18-74 years). The questionnaire with specific questions from the internationally recognized self-efficacy scale “The General Self-Efficacy Scale (GSE)” was used. The obtained results will follow the correlation of the self-efficacy level of the patients with the paternalistic, consumerist, participative and training physician relationship.